2021
DOI: 10.3390/su13052620
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Chocolates Enriched with Untreated Cocoa Bean Shells and Cocoa Bean Shells Treated with High-Voltage Electrical Discharge

Abstract: Recently, the enrichment of chocolate has become a very interesting topic, along with the management of food industry by-products, such as cocoa shells. Cocoa shells could be a great raw material for the cocoa industry, both for economical reasons (maximized utilization of cocoa beans) and for their functional properties (increased fiber content). In this research, we used untreated and high-voltage electrical discharge (HVED)-treated cocoa shells in the production of chocolate. Different proportions of cocoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…Moreover, saponins are Comparing the results obtained with similar studies, Kovač et al ( 2021) [34] obtained 0.28 mg of catechin and 0.27 mg of epicatechin per g of CBS using high-voltage electrical discharge (HVED) for 30 min with a solid/liquid ratio of 1:30, similar to the values obtained in this work. However, Barišić et al (2021) [35], who evaluated the use of HVED on the extraction of CBS phenolic components in water (3% w/v), obtained extracts with maximum amounts of catechin and epicatechin of 0.07 and 0.08 mg/g, respectively, after 15 min of treatment, significantly lower values than those obtained in the present work when the pH was adjusted to 4.…”
Section: Saponinscontrasting
confidence: 79%
“…Moreover, saponins are Comparing the results obtained with similar studies, Kovač et al ( 2021) [34] obtained 0.28 mg of catechin and 0.27 mg of epicatechin per g of CBS using high-voltage electrical discharge (HVED) for 30 min with a solid/liquid ratio of 1:30, similar to the values obtained in this work. However, Barišić et al (2021) [35], who evaluated the use of HVED on the extraction of CBS phenolic components in water (3% w/v), obtained extracts with maximum amounts of catechin and epicatechin of 0.07 and 0.08 mg/g, respectively, after 15 min of treatment, significantly lower values than those obtained in the present work when the pH was adjusted to 4.…”
Section: Saponinscontrasting
confidence: 79%
“…Cakes obtained employing 75% CBS powder presented satisfactory sensorial and nutritional properties (100 g TE/g CBS, 92 mg GAE/100 g CBS and 7.8 mg anthocyanins/100 g CBS). Bariŝić et al, 2021 [143] employed untreated and treated CBS with high-voltage electrical discharge (HVED) at different proportions (0-15%) to produce enriched chocolate. They reported that milk chocolate with 5% and dark chocolate with 15% of CBS, both untreated and treated, obtained a positive acceptance of consumers mainly due to the softness and darkness of the final products.…”
Section: Food Ingredientmentioning
confidence: 99%
“…Chocolate is a range of foods derived from cocoa (Theobroma cacao) seeds and it is becoming one of the most popular sweet products worldwide [1][2][3]. Chocolate is a complex mixture of cocoa and finely powdered sugar in a continuous fat phase, mainly cocoa butter, to produce a solid confectionery [4][5][6].…”
Section: Introductionmentioning
confidence: 99%